(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Emphysematous pyelonephritis (EPN) is an acute severe necrotizing infection of the renal parenchyma and its surrounding tissues that is caused by the presence of gas in the renal parenchyma, collecting system or perinephric tissue.The present study was intended to assess the functional status of the emphysematous kidney recovered from infection after treatment. Methods: This prospective study was conducted on 50 consecutive cases of emphysematous pyelonephritis, who were admitted in BIRDEM General Hospital from January 2011 to June 2012. Patients with EPN were selected after taking history, clinical examination and radiological image findings. Based on clinical parameter and radiological grading, patients were categorized for medical or surgical intervention. The forms of surgeries were open drainage or nephrectomy. Renal parenchymal destruction more than 50% on CT required nephrectomy. Results: The mean age of the patients at diagnosis was 47.5 ± 11.8 years (range: 26-70 years). The patients were predominantly female (82%), invariably diabetic and primarily presented with fever (88%) and loin pain (82%) followed by dysuria (60%). Over three-quarters (78%) of the patients had poor glycemic control (HbA1c >7%) and over half (54%) were classified as having class 1 or 2 disease and the rest had class 3 and 4 diseases. Escherichia coli was the commonest pathogen found in urine cultures (70%). Over half (56%) received medical treatment alone. In the surgical intervention group, patients were mostly toxic with spreading or severe localized infection, fever and were deteriorating or static even after three days of aggressive intravenous antibiotic treatment. Of the 22 patients who underwent surgery, nephrectomy was performed in 8(16%) and open drainage in 14(28%) cases. The overall survival rate was 94%. Average serum creatinine level was found to decrease gradually during follow up. The function of the preserved kidney was found to improve in the subsequent follow up. Conclusion: Emphysematous pyelonephritis predominantly affects diabetic females. Kidney preservation should be the primary target in treating EPN. Adequate resuscitation, diabetic control and parenteral antibiotic are the treatment of choice. Rapid drainage and nephrectomy should be performed in advanced stages. The focus of management of patients with emphysematous pyelonephritis should not only to improve survival but also salvage of the renal unit, for the affected kidney may still function once the infection is eradicated. Ibrahim Card Med J 2017; 7 (1&2): 57-63